EXTREME RAINFALL EVENT IDENTIFICATION BASED ON TROPICAL RAINFALL MEASURING MISSION (TRMM) DATA TEMPORALLY (Case Study: Soreang) - ABISENO (NIM : 12807006); Pembimbing : Drs. Zadrach L. Dupe, M.Si., PRATIKTO
Extreme rainfall is one of the meteorological phenomenon that have the most severe damaging effects and reported that the rainfall that occurred on November 17, 2012 in Soreang was the biggest rain they had experienced in the last few years. Tropical Rainfall Measuring Mission satellite (TRMM) is a meteorological satellites that provide up-to-date rainfall data and can show a fairly good rainfall pattern and the TRMM 3B42 data is the rain rate data with an interval of 3 hours that always available after a month of observation. In this study to identify whether the incident on November 17, 2012 at Soreang can be categorized as extreme rain is by finding the probability of extreme rainfall events using the Cumulative Distribution Function (CDF) with the TRMM data that has been corrected by bias correction process as validation against observational data. Probability of rain occurrence on November 17, 2012 for the daily data is at 1.86% of the entire data set and the 3-hourly data is at 0.6% of the entire data set. Comparising the Seasonal distribution data, probability of occurrence of rain on November 17, 2012 with a daily interval is 1.13% and with an interval of 3-hourly is 0.94%, so it can be said that the rain events with an interval of 3 hour-ly is more extreme than the daily interval .